2023
DOI: 10.3390/curroncol30040280
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy in Early-Stage Non-Small Cell Lung Cancer (NSCLC): Current Evidence and Perspectives

Abstract: Lung cancer is the leading cause of cancer deaths in the world. Surgery is the most potentially curative therapeutic option for patients with early-stage non-small cell lung cancer (NSCLC). The five-year survival for these patients remains poor and variable, depending on the stage of disease at diagnosis, and the risk of recurrence following tumor resection is high. During the last 20 years, there has been a modest improvement in the therapeutic strategies for resectable NSCLC. Immune checkpoint inhibitors (IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…26 Immunotherapy, specifically ICIs, has emerged as a promising therapeutic strategy for the treatment of various tumors. 27,28 Given the rising incidence of lung cancer, there is growing interest among clinicians in the potential therapeutic benefits of combining cemiplimab with chemotherapy, as demonstrated in the EMPOWER-Lung 3 clinical trial. A recent 2-year follow-up analysis from part 2 of the EMPOWER-Lung 3 trial demonstrated sustained benefits of cemiplimab plus chemotherapy versus chemotherapy alone in patients with advanced NSCLC after 28.4 months of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…26 Immunotherapy, specifically ICIs, has emerged as a promising therapeutic strategy for the treatment of various tumors. 27,28 Given the rising incidence of lung cancer, there is growing interest among clinicians in the potential therapeutic benefits of combining cemiplimab with chemotherapy, as demonstrated in the EMPOWER-Lung 3 clinical trial. A recent 2-year follow-up analysis from part 2 of the EMPOWER-Lung 3 trial demonstrated sustained benefits of cemiplimab plus chemotherapy versus chemotherapy alone in patients with advanced NSCLC after 28.4 months of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The synergistic combination of chemotherapy and immunotherapy was becoming rather evident, with preclinical data from Martin-Ruiz et al demonstrating a significant difference in tumor regression rates in the arm that received immunotherapy plus cisplatin versus immunotherapy alone [49]. In light of NADIM's results and building upon them, the NADIM II trial followed [50]. In this randomized, phase 2, open-label trial, 86 patients clinically staged IIIA-B, 35% of which presented with multi-stationed N2 disease, were randomly assigned to receive three cycles of doublet chemotherapy compared to nivolumab plus chemotherapy, followed by surgery and then adjuvant nivolumab for six months.…”
Section: Perioperative Immunotherapymentioning
confidence: 99%
“…Around 40% of early NSCLC patients seem to gain no benefit from chemo-immunotherapy regimens, highlighting the unmet need for customized patient care [50]. Amongst other similar parameters, such as tumor mutational burden (TMB), CD8+ invasion rates, and absence of immunosuppressive cell subsets, PD-L1 expression has emerged as the most clinically significant biomarker to assess response to immunotherapy [16].…”
Section: Pd-l1 Expressionmentioning
confidence: 99%
“…Neo-adjuvant and perioperative therapies are an emerging topic in the multi-modal treatment landscape of early-stage NSCLCs ( 1 ). A growing number of clinical trials evaluates the use of either IO, or combined IO-chemotherapy (IO-CTx) or targeted therapies in this particular setting ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of clinical trials evaluates the use of either IO, or combined IO-chemotherapy (IO-CTx) or targeted therapies in this particular setting ( Table 1 ). Biologically, systemic therapy before surgery (including perioperative strategies) induces profound and long-lasting changes of the tumor microenvironment (TME), encompassing multi-faceted immune cells, cancer-associated fibroblast (CAF) and tumor vasculature ( 1 , 8 ).…”
Section: Introductionmentioning
confidence: 99%